Identifying Suitable Areas for Urban Development in Rampur Municipality of Palpa District, Nepal (Journal on Geoinformatics, Nepal, 2017)
Identifying suitable areas for urban development is one of the critical issues of urban planning in hilly areas in Palpa district. The study illustrates the use of GIS suitability criteria and weighted overlay analysis technique for selection of suitable areas for urban development in Rampur municipality. The main objectives of this research is to identifying suitable areas for urban development of Rampur Municipality, Palpa. For this purpose panchromatic and multispectral satellite image data were used to generate for land use land cover map using digitalization and visual interpretation method in ArcGIS software. The criteria using five parameters i.e. geology, elevation, slope, aspect, and Land Use Land Cover (LULC) and the method of Suitability Criteria and Weighted Overlay Analysis were used for identifying the suitable areas for urban development. The eight categories are Agriculture, Commercial, Forest, Industrial, Public Use, Residential, Road and Water Bodies were used for LULC map. The result of this research shows highly suitable areas of Rampur municipality is 5.54 Sq. Km. and it covers 4.49% for suitable areas for urban development.